A Critical Analysis of the Regulatory Framework and Evidentiary Practices under Law No. 12 of 2022 on Sexual Violence Crimes - Irpan Suriadiata; Janou Willems (Syura: Journal of Law, 2026)
Law No. 12 of 2022 on Sexual Violence Crimes was enacted as a specific legal instrument to strengthen the protection of victims of sexual violence in Indonesia. However, the evidentiary provisions contained in the law raise significant legal concerns regarding the balance between victim protection and the protection of suspects' rights, particularly in relation to the presumption of innocence and due process of law. This study aims to analyze the regulation and application of evidentiary practices in sexual violence cases, examine the legal challenges in balancing victim protection with the rights of suspects, and assess the legal implications of disparities in protection between both parties under Law No. 12 of 2022. This research employs a normative legal method using statutory, case law, and conceptual approaches. The data sources consist of legislation, judicial decisions, legal doctrines, and relevant scholarly literature. The findings reveal that the evidentiary framework under the Sexual Violence Crimes Law potentially weakens the presumption of innocence due to the tendency to rely on victim and psychologist testimony without sufficient objective corroborative evidence. Furthermore, there is a shift in the standard of proof from the principle of beyond a reasonable doubt toward emotional justification, which may threaten both procedural and substantive justice. This study contributes a critical legal analysis of evidentiary practices under the Sexual Violence Crimes Law and proposes strengthening the balance between victim protection and the constitutional rights of suspects within Indonesia’s criminal justice system.